EMU One Year On (Washington Organization for Economic Cooperation & Development, 2000)
Annotation Europe's single currency was launched a bit more than a year ago for eleven of the fifteen countries of the Union. This study assesses economic developments and policies during the inaugural year of the new regime. It analyses the economic performance and prospects of the euro area as a whole, and highlights to what extent aggregate trends are shaped by convergence or divergence at national or regional levels. Macroeconomic policies are discussed in depth. The common monetary policy carried out by the Eurosystem and the underlying framework are scrutinised, as is the co-ordination of national fiscal policies against the background of the Stability and Growth Pact. A special chapter is devoted to the links between structural features and policies on the one hand and macroeconomic performance on the other. It argues that broad-based and properly designed structural reforms would boost Europe's economic potential significantly and ease macroeconomic policy trade-offs. Book jacket.
Keywords: Euro; Europe -- Economic Integration; European Union Countries; Monetary Policy -- European Economic Community Countries; Monetary Unions